The 2dF QSO Redshift Survey - VI. Measuring Lambda and Beta from Redshift-space Distortions in the Power Spectrum - Outram, P; Hoyle, F; Shanks, T; Boyle, B; Croom, S; Loaring, N; Miller, L; Smith, R (2001)
When the 2dF QSO Redshift Survey (2QZ) is complete, a powerful geometric test for the cosmological constant will be available. By comparing the clustering along and across the line of sight and modelling the effects of peculiar velocities and bulk motions in redshift space, geometric distortions, which occur if the wrong cosmology is assumed, can be detected. In this paper we investigate the effect of geometric and redshift-space distortions in the power spectrum parallel and perpendicular to the observer's line of sight. Ballinger et al. developed a model to estimate the cosmological constant, $Λ$, and the important parameter $β ≈ Ω_m^{0.6}/b$ from these distortions. We apply this model to a detailed simulation of the final 25k 2QZ, produced using the Virgo Consortium's huge {\it Hubble Volume} N-body $Λ$-CDM light cone simulation. We confirm the conclusions of Ballinger et al.; the shape of the redshift-space and geometric distortions are very similar. When all the uncertainties are taken into account we find that only a joint $Λ - β$ constraint is possible. By combining this result with a second constraint based on mass clustering evolution, however, we can make significant progress. We predict that this method should allow us to constrain $β$ to approximately $±0.1$, and $Ω_{m}$ to $±0.25$ using the final catalogue. We apply the method to the 2QZ catalogue of 10000 QSOs and find that this incomplete catalogue marginally favours a $Λ$ cosmology.